Designing a context-based strategy for teaching and learning of mathematics word problems - Sibaya, K. T. (University of the Free State, 2019)
This study aims to design a context-based strategy for the teaching and learning of mathematical WP for Afromontane learners. In the context of this study, Afromontane learners form part of the social construct of people that live and subsist in mountainous places, drawing from the wealth of their cultural and indigenous knowledge. This wealth of knowledge, which has sustained the Afromontane or Indigenous people, is often marginalised in the teaching and learning of mathematics, particularly WP. For these apparent reasons, I found it necessary to design a context-based strategy that would enhance teaching and learning of mathematical WP for Afromontane learners. In order to attain this goal, firstly, I opted to utilise Community Cultural Wealth as a lens through which I looked into the challenges experienced by these learners in their attempts to use these indigenous skills. Secondly, I employed Participatory Action Research (PAR) as the research methodology with a view that would also assist to generate data from the research site with the aid of the research participants. Critical Discourse Analysis (CDA) is a technique employed to analyse and interpret data generated from the research field, taking into consideration the three levels of analysing and interpreting data, namely: textual analysis, discursive practices and social structures. Key findings of the study include: Inadequate skills to teach mathematical WP within the context of the learners as a remaining challenge that forces some teachers to opt for using traditional way of teaching (rote teaching and algorithmic approach) • Teachers still lack skills to integrate indigenous games with mathematical WP • Abstract teaching and learning of mathematical WP still remain a challenge • The creation of a learning environment in the classroom setting during tuition time still remains a challenge Based on the findings of the study, the following is recommended: • Collaborative teaching and learning mathematical WP with the Hands-on strategy • The use of indigenous games as a tool to bridge a gap between traditional and western practices • Teaching and learning mathematical WP through manipulatives • Connection of the conceptual world with the real world
Thesis (Ph.D. (Curriculum Studies))--University of the Free State, 2019
Keywords: Afromontane learners; Context-based strategy; Word problems